2012
DOI: 10.1002/ceat.201200371
|View full text |Cite
|
Sign up to set email alerts
|

Kinetics of o‐Xylene Combustion over a Pt/Alumina Catalyst

Abstract: Abstracto‐Xylene combustion in air over a Pt/γ‐Al2O3 catalyst was investigated in a laboratory reactor at low concentrations typical for depollution applications. The results evidenced a slightly negative influence of o‐xylene concentration on combustion rate. A kinetic model of the combustion process was developed by using the Langmuir‐Hinshelwood mechanism, assuming the surface reaction between adsorbed oxygen atoms and adsorbed o‐xylene molecules as controlling step. The rate expression includes the influen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 24 publications
1
13
0
Order By: Relevance
“…As already mentioned, an important issue in the application of the integral method using the fixed‐bed conversion data is the occurrence of axial temperature gradients. The results of Ordóñez et al 25 and some of our previous results 14, 15 demonstrate that, for diluted catalysts, the axial temperature gradients along the catalyst bed arising for VOC conversions up to around 40 % can be neglected. In the present study, the kinetic parameter estimation based on the integral method will be performed in two variants, one using conversion values below 10 % (in comparison with the differential method) and the other for conversions up to 20 % (in order to reduce the influence of measurement errors, keeping the values of the axial temperature gradients negligible).…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…As already mentioned, an important issue in the application of the integral method using the fixed‐bed conversion data is the occurrence of axial temperature gradients. The results of Ordóñez et al 25 and some of our previous results 14, 15 demonstrate that, for diluted catalysts, the axial temperature gradients along the catalyst bed arising for VOC conversions up to around 40 % can be neglected. In the present study, the kinetic parameter estimation based on the integral method will be performed in two variants, one using conversion values below 10 % (in comparison with the differential method) and the other for conversions up to 20 % (in order to reduce the influence of measurement errors, keeping the values of the axial temperature gradients negligible).…”
Section: Resultsmentioning
confidence: 66%
“…The catalyst used was Pt/ γ ‐Al 2 O 3 containing 0.5 wt % Pt, produced by Engelhard (ESCAT 26). Previous studies performed on the same catalyst, on the combustion of VOC with comparable reactivity, reported that the influence of internal diffusion on the process kinetics is negligible for catalyst particle sizes lower than 250 μm 14. Hence, all the experiments reported further in this study were performed with catalyst particles in the size range of 50–250 μm.…”
Section: Methodsmentioning
confidence: 93%
“…This technology was first used on the Japanese market in 1994, coupled to a lean burn engine [3], and was introduced in Europe by Toyota in 2005, with the diesel particulate NO x reduction (DPNR) designation [9][10][11][12][13][14]. The model NSR catalyst usually contains three components: a NO x storage component such as Ba, a NO x oxidation/reduction precious metal such as Pt, and a high-surface-area support, usually Al 2 O 3 [15][16][17]. A typical NSR consists of fine porous ceramic monoliths containing thousands of parallel channels through which the ex-haust gases are directed.…”
Section: Introductionmentioning
confidence: 99%
“…The development of a suitable kinetic model for catalytic combustion of VOCs represents a key element in the prediction of the reaction mechanism . The catalytic combustion kinetics must be taken into account for designing a reliable catalytic combustion reactor and improving the catalytic combustion performance of the existing catalyst .…”
Section: Introductionmentioning
confidence: 99%